Intercultural Communication in Contexts - Martin Judith N (Mc Graw-Hill, 2009)
This popular text addresses the core issues and concerns of intercultural communication by integrating three different perspectives: the social psychological, the interpretive, and the critical. The dialectical framework, integrated throughout the book, is used as a lens to examine the relationship of these research traditions. This text is unique in its emphasis on the importance of histories, popular culture, and identities. The new edition features expanded discussion on globalization, computer-mediated technologies, and the role of religion in global and domestic contexts and how they relate to intercultural communication.